THE EFFECT OF ENTREPRENEURSHIP EDUCATION ON INTERESTS OF ENTREPRENEURSHIP THROUGH SELF AWARENESS IN STUDENTS IN SURABAYA - Candraningrat Candraningrat (Universitas 17 Agustus 1945 Surabaya, 2020)
This study aims to determine the effect of entrepreneurship education and self-awareness variables on entrepreneurial interest in students in the city of Surabaya. The data analysis technique used is the SEM-PLS analysis through the Warp PLS 6.0 program. Data collection techniques by conducting surveys through a questionnaire distributed to respondents by purposive sampling. The population in this study were all students in the city of Surabaya who were taking and who had passed an entrepreneurship course, so the sample determined in this study were 100 students in the city of Surabaya who were making and who had passed an entrepreneurship course with active status. This research is classified as quantitative research. This study provides findings that the variables of entrepreneurship education and self-awareness have a significant and positive effect on entrepreneurial interest. Also, entrepreneurship education variables affect the interest in entrepreneurship through self-awareness.